Studi Analisis Pembinaan Prestasi Ekstrakulikuler Futsal Di SMAN 10 Kota Bengkulu - riyandi sudrajat; yarmani yarmani; santun sihombing (Universitas Bengkulu, 2020)
This study aims to find out about futsal extracurricular achievements at SMAN 10 Kota Bengkulu. The problem examined in this study is how the Development of Futsal Extracurricular Participant Development at SMAN 10 Kota Bengkulu. The data sources of this study include coaches, trainers, and extracurricular participants, as well as documents. In this study using qualitative descriptive methods. Data collection techniques use observation, questionnaire, interview, and documentation techniques. The sample was studied by futsal participants at SMAN 10 Kota Bengkulu, totaling 28 students. From the data obtained, it can be concluded that, 1) The making of training programs and recruitment of extracurricular participants has not been going well, plus it is not supported by adequate facilities and infrastructure. 2) There is no specific selection to take part in Futsal extracurricular activities at SMAN 10 Kota Bengkulu. 3). The direction of futsal extracurricular activities at SMAN 10 Kota Bengkulu in terms of time and discipline has gone well. 4). Funding sources for futsal extracurricular activities at SMAN 10 Kota Bengkulu do not have and specifically from schools.